2022
DOI: 10.3389/fmed.2021.775604
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Aid Colonoscopy Vs. Conventional Colonoscopy for Polyp and Adenoma Detection: A Systematic Review of 7 Discordant Meta-Analyses

Abstract: Objectives: Multiple meta-analyses which investigated the comparative efficacy and safety of artificial intelligence (AI)-aid colonoscopy (AIC) vs. conventional colonoscopy (CC) in the detection of polyp and adenoma have been published. However, a definitive conclusion has not yet been generated. This systematic review selected from discordant meta-analyses to draw a definitive conclusion about whether AIC is better than CC for the detection of polyp and adenoma.Methods: We comprehensively searched potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recent metaanalyses provide abundant evidence demonstrating the value of a computer-aided polyp detection (CADe) system by increasing the ADR and reducing missed adenomas [7,8,9,10]. Despite the impressive results, many studies have been criticized for having a low baseline ADR, raising the question of whether similar results would have been obtained had the baseline ADR been higher [6,7,8,9]. Furthermore, previous meta-analyses concluded that CADe could aid in detecting only diminutive polyps while not increasing the detection of advanced adenoma [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent metaanalyses provide abundant evidence demonstrating the value of a computer-aided polyp detection (CADe) system by increasing the ADR and reducing missed adenomas [7,8,9,10]. Despite the impressive results, many studies have been criticized for having a low baseline ADR, raising the question of whether similar results would have been obtained had the baseline ADR been higher [6,7,8,9]. Furthermore, previous meta-analyses concluded that CADe could aid in detecting only diminutive polyps while not increasing the detection of advanced adenoma [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in artificial intelligence technology over the past decade have opened up new possibilities for overcoming human error during colonoscopy procedures [6]. Recent metaanalyses provide abundant evidence demonstrating the value of a computer-aided polyp detection (CADe) system by increasing the ADR and reducing missed adenomas [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The latest technology is using real-time artificial intelligence systems to detect and/or characterize polyps [5]. This new technology has already been shown to increase the ADR as well as the adenomas detected per patient [6]. This is achieved mostly by the detection of small and diminutive adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…They all show a more or less significant increase in detection of small adenomas. The same results are summarized over and over again in no less than 16 meta-analyses [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], plus a protocol for a further one [36], as well as a meta-analysis of some of these meta-analyses [37]! "The question relates to the ultimate clinical relevance of increasing ADR from high to even higher levels …, we still do not know whether we have a cutoff ADR level, above which there is no further improvement in cancer prevention.…”
mentioning
confidence: 97%